Migration patterns and land use by immigrants under a changing frontier society in the Peruvian Amazon - Ichikawa, Masahiro; Ricse Tembladera, Auberto; Ugarte, Julio; Kobayashi, Shigeo (Japan Soc Tropical Ecology, 2023)
One of main factors identified as explaining forest loss and degradation in the Selva (the Peruvian Amazon) is the migration of people from the Sierra (Andes highlands), where agricultural conditions are severe, to forest areas in the Selva in search of new land. This paper aims at clarifying the characteristics and process of migration based on interviews with local people near Pucallpa, Ucayali Department, where forest loss and degradation has advanced in recent decades. In the study area, forest loss and degradation progressed by commercial logging after construction of a road connecting between Lima and Pucallpa in 1943. After logging, stock-farming companies and immigrants entered the area, and land uses other than high forest have been expanding. Today, the study area is occupied by people who have immigrated since the 1960s. Many of them earned income by logging until the 1980s, while today almost of them make a livelihood by agriculture, stock farming, or tree planting. As a result of these economic activities, there are substantial areas of mixed shrubs and grass in the study area today. This paper clarifies two points. First, the majority of immigrants were born not in the Sierra, but in the Selva, for instance as part of the expanding population in the Departments of San Martin and Amazonas. The main stream of migration is from parts of the Selva where immigrants had started reclamation in earlier days to other parts of the Selva with still abundant forests (such as the study area). Second, most migrants were not born in a rural area, but in Pucallpa, a developing urban area in the Selva. Pucallpa is also an important place for step migrants who stayed there for a while and worked temporarily before immigrating to the study area. The urban area has gained an important role in migration to forests in the Selva as a place of birth of migrants and for its function in step migration.